The effect of supply chain glitches on shareholder wealth - Hendricks, Kevin B.; Singhal, Vinod R. (Journal of Operations Management, 2003)
This paper estimates the shareholder wealth affects of supply chain glitches that resulted in production or shipment delays. The results are based on a sample of 519 glitches announcements made during 1989–2000. Shareholder wealth affects are estimated by computing the abnormal stock returns (actual returns adjusted for industry and market‐wide influences) around the date when information about glitches is publicly announced. Supply chain glitch announcements are associated with an abnormal decrease in shareholder value of 10.28%. Regression analysis is used to identify factors that influence the direction and magnitude of the change in the stock market’s reaction to glitches. We find that larger firms experience a less negative market reaction, and firms with higher growth prospects experience a more negative reaction. There is no difference between the stock market’s reaction to pre‐1995 and post‐1995 glitches, suggesting that the market has always viewed glitches unfavorably. Capital structure (debt–equity ratio) has little impact on the stock market’s reaction to glitches. We also provide descriptive results on how sources of responsibility and reasons for glitches affect shareholder wealth.